Narodowe rekolekcje i rozrachunki, czyli literatura polska wobec pierwszej wojny światowej. Wybór = National retreats and settlements, or Polish literature towards the First World War. The choice - Olszewska, Maria Jolanta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The First World War is one of the most important breakthrough moments in modern history. Becauseof its historical importance has been called the Great War white people, which gave it the status ofa symbol. The space, which is pending dispute induce by the war for the right to speak the truthabout the war, becomes discussion of modern man and the world`s literature.
Keywords: I (pierwsza) wojna światowa; literatura polska